Dopamine/Tyrosine Hydroxylase Neurons of the Hypothalamic Arcuate Nucleus Release GABA, Communicate with Dopaminergic and Other Arcuate Neurons, and Respond to Dynorphin, Met-Enkephalin, and Oxytocin - Zhang, Xiaobing (J Neurosci, 2015)
We employ transgenic mice with selective expression of tdTomato or cre recombinase together with optogenetics to investigate whether hypothalamic arcuate (ARC) dopamine/tyrosine hydroxylase (TH) neurons interact with other ARC neurons, how they respond to hypothalamic neuropeptides, and to test whether these cells constitute a single homogeneous population. Immunostaining with dopamine and TH antisera was used to corroborate targeted transgene expression. Using whole-cell recording on a large number of neurons (n = 483), two types of neurons with different electrophysiological properties were identified in the dorsomedial ARC where 94% of TH neurons contained immunoreactive dopamine: bursting and nonbursting neurons. In contrast to rat, the regular oscillations of mouse bursting neurons depend on a mechanism involving both T-type calcium and A-type potassium channel activation, but are independent of gap junction coupling. Optogenetic stimulation using cre recombinase-dependent ChIEF-AAV-DJ expressed in ARC TH neurons evoked postsynaptic GABA currents in the majority of neighboring dopamine and nondopamine neurons, suggesting for the first time substantial synaptic projections from ARC TH cells to other ARC neurons. Numerous met-enkephalin (mENK) and dynorphin-immunoreactive boutons appeared to contact ARC TH neurons. mENK inhibited both types of TH neuron through G-protein coupled inwardly rectifying potassium currents mediated by δ and μ opioid receptors. Dynorphin-A inhibited both bursting and nonbursting TH neurons by activating κ receptors. Oxytocin excited both bursting and nonbursting neurons. These results reveal a complexity of TH neurons that communicate extensively with neurons within the ARC. SIGNIFICANCE STATEMENT Here, we show that the great majority of mouse hypothalamic arcuate nucleus (ARC) neurons that synthesize TH in the dorsomedial ARC also contain immunoreactive dopamine, and show either bursting or nonbursting electrical activity. Unlike rats, the mechanism underlying bursting was not dependent on gap junctions but required T-type calcium and A-type potassium channel activation. Neuropeptides dynorphin and met-enkephalin inhibited dopamine neurons, whereas oxytocin excited them. Most ventrolateral ARC TH cells did not contain dopamine and did not show bursting electrical activity. TH-containing neurons appeared to release synaptic GABA within the ARC onto dopamine neurons and unidentified neurons, suggesting that the cells not only control pituitary hormones but also may modulate nearby neurons.